Carriage of antibiotic resistance genes to treatments for chlamydial disease in koalas (Phascolarctos cinereus): A comparison of occurrence before and during catastrophic wildfires - Fiona K. McDougall; Wayne S.J. Boardman; Natasha Speight; Tamsyn Stephenson; Oliver Funnell; Ian Smith; Petra L. Graham; Michelle L. Power (One Health, 2023)
Growing reports of diverse antibiotic resistance genes in wildlife species around the world symbolises the extent of this global One Health issue. The health of wildlife is threatened by antimicrobial resistance in situations where wildlife species develop disease and require antibiotics. Chlamydial disease is a key threat for koalas in Australia, with infected koalas frequently entering wildlife hospitals and requiring antibiotic therapy, typically with chloramphenicol or doxycycline. This study investigated the occurrence and diversity of target chloramphenicol and doxycycline resistance genes (cat and tet respectively) in koala urogenital and faecal microbiomes. DNA was extracted from 394 urogenital swabs and 91 faecal swabs collected from koalas in mainland Australia and on Kangaroo Island (KI) located 14 km off the mainland, before (n = 145) and during (n = 340) the 2019–2020 wildfires. PCR screening and DNA sequencing determined 9.9% of samples (95%CI: 7.5% to 12.9%) carried cat and/or tet genes, with the highest frequency in fire-affected KI koalas (16.8%) and the lowest in wild KI koalas sampled prior to fires (6.5%). The diversity of cat and tet was greater in fire-affected koalas (seven variants detected), compared to pre-fire koalas (two variants detected). Fire-affected koalas in care that received antibiotics had a significantly higher proportion (p < 0.05) of cat and/or tet genes (37.5%) compared to koalas that did not receive antibiotics (9.8%). Of the cat and/or tet positive mainland koalas, 50.0% were Chlamydia-positive by qPCR test. Chloramphenicol and doxycycline resistance genes in koala microbiomes may contribute to negative treatment outcomes for koalas receiving anti-chlamydial antibiotics. Thus a secondary outcome of wildfires is increased risk of acquisition of cat and tet genes in fire-affected koalas that enter care, potentially exacerbating the already significant threat of chlamydial disease on Australia's koalas. This study highlights the importance of considering impacts to wildlife health within the One Health approach to AMR and identifies a need for greater understanding of AMR ecology in wildlife.